2016
DOI: 10.5897/ajar2016.10910
|View full text |Cite
|
Sign up to set email alerts
|

Proximate composition, amino acid profile and some anti-nutrients of Tithonia diversifolia cut at two different times

Abstract: The experiment assessed the proximate and amino acid compositions, metabolizable energy and antinutrient constituents of Tithonia diversifolia leaf meal (TDLM) harvested separately in the months of May and September, respectively using standard laboratory methods. The crude protein (20.5±0.1%), crude fibre (18.8±0.01%) and ash (14±0.1%) significantly (p˂0.05) increased in TDLM for September cutting than that of May (18.05±0.1%, 11.17±0.3% and 13.01±0.1%, respectively). All the anti-nutrient factors (ANFs), nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Also, it can affect the health and production of animals through mechanisms of decreasing nutrient intake, digestive and RONI PAZLA 1,♥ , NOVIRMAN JAMARUN 1,♥♥ , MARDIATI ZAIN 1 , GUSRI YANTI 2 , RIKI HISKIA CHANDRA 3 absorption disorders and causing other adverse side effects. Oluwasola and Dairo (2016) stated that the most antinutrient content in tithonia was phytic acid, 79.2 mg/100gr. The high phytic acid content in tithonia causes a bitter taste, so it is not liked by livestock.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it can affect the health and production of animals through mechanisms of decreasing nutrient intake, digestive and RONI PAZLA 1,♥ , NOVIRMAN JAMARUN 1,♥♥ , MARDIATI ZAIN 1 , GUSRI YANTI 2 , RIKI HISKIA CHANDRA 3 absorption disorders and causing other adverse side effects. Oluwasola and Dairo (2016) stated that the most antinutrient content in tithonia was phytic acid, 79.2 mg/100gr. The high phytic acid content in tithonia causes a bitter taste, so it is not liked by livestock.…”
Section: Introductionmentioning
confidence: 99%
“…T. diversifolia grows in the highlands and contains anti-nutritional substances, such as phytic acid, which binds phosphor. The phytic acid content of the tithonia plant is 79.2mg/kg (Oluwasola and Dairo 2016). Furthermore, the phytic acid that enters the rumen will be degraded by microbes, which produce phytase enzymes, thereby allowing the release of bound phosphorus into available form (Pazla et al 2021b;Pazla et al 2021c).…”
Section: Nutrient Consumptionmentioning
confidence: 99%
“…Tithonia is also rich in P mineral, which can potentially increase the number of rumen bacterial populations (Fasuyi et al 2010;Adrizal et al 2021;Pazla et al 2021b). Oluwasola and Dairo (2016) reported that tithonia plants are also rich in amino acids. The mixture of tithonia with elephant grass as a fiber source in ECDG ration can optimize intake, digestibility, and milk production (Pazla et al 2022).…”
Section: Introductionmentioning
confidence: 99%